TUNJANGAN PROFESI SEBAGAI UPAYA PENINGKATAN KOMPETENSI GURU UNTUK MEWUJUDKAN GURU PROFESIONAL - Yuliandri, Jimmi; Tahrun, Tahrun (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
This research was conducted to reveal the improvement of teachersâ competence who have received professional allowances in realizing professional teachers. The data were obtained through interviews, documentation and observation. Improving the teachersâ competence is expected in order to improve the quality of education. Only then the professional teacher is capable of conducting learning and succeeding in bringing the learner into the world of life according to todayâs needs and challenges. Conversely, the unwillingness and inability of teachers to adjust their insight and competence with the demands of the development would be one of the obstacles to the achievement of educational and learning objectives.Â Keywords: Professional Allowances, Improvement of Teachersâ Competence, Professional Teacher